Cost-Effectiveness Analysis: New Approaches in Decision-Making. - Ferrara, William L.; Bruns, William J. (The Accounting Review, 1968)
Reviews the book "Cost-Effectiveness Analysis: New Approaches in Decision-Making," edited by Thomas A. Goldman.